Enhancing Digital Political Literacy to Improve Migrant Voter Participation: A Case Study in Penang, Malaysia (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The development of digital literacy is essential for enabling individuals to distinguish between facts and opinions, verify the accuracy of information, and understand the influence of social media algorithms. With the rise of post-truth politics, where the boundaries between truth and falsehood blur, voters are increasingly susceptible to misinformation and political propaganda. Digital literacy, particularly in the political context, empowers citizens to make informed decisions, fostering critical thinking and responsible social media use. This can be achieved through educational programs, collaborations among governments, educational institutions, and civil society organizations, and campaigns promoting the importance of digital literacy. Social media platforms also play a crucial role in combating misinformation by enhancing hoax detection technology and providing warning labels for unverified content. The urgency of digital political literacy is particularly relevant in the context of elections, where misinformation, fake news, and disinformation can lead to social polarization and confusion. The use of digital communication technologies, which decentralize information sources, has transformed the political landscape, making cyberspace an important platform for both political campaigning and public expression. By developing digital political literacy, citizens are better equipped to evaluate political offers, access reliable information, and make informed choices. This study explores the importance of digital political literacy in combating misinformation, particularly among Indonesian migrant workers. In the era of post-truth politics, where falsehoods dominate digital spaces, fostering critical digital skills is essential. The paper advocates for educational programs and collaborative initiatives to empower migrant voters in making informed electoral decisions, thereby enhancing democratic participation and reducing polarization.